Positive Affects Inducer on Software Quality - Syed Abdullah, Sharifah Lailee; Omar, Mazni; Abdul Hamid, Mohd Nasir; Ismail, Che Latifah; Jusoff, Kamaruzaman (2009)
This paper presents an early empirical study on an agile methodology (Extreme Programming) using Positive Affect metric. The question of interest is whether an agile methodology has any distinct outcome on the positive affectivity of the software developers. And whether these affects will contribute to the quality of software produced. Quantitative methods were utilized, including participative observation and simple statistical tests such as Spearman Correlation and Mann-Whitney test. The results showed that Extreme Programming has positive affectivity which leads to the increase in software quality. This study suggests that when people experience joy and mild contentment, they are more likely to be more creative over wider range of problems, become more resilient over time and are more likely to develop long-term plans and goals.